Low-intensity transcranial focused ultrasound of the amygdala modulates neural activation during emotion processing - Kathryn C. Jenkins; Kathryn C. Jenkins; Katherine Koning; Arman Mehzad; John LaRocco; Jagan Jimmy; Jagan Jimmy; Shiane Toleson; Shiane Toleson; Kevin Reeves; Stephanie M. Gorka; Stephanie M. Gorka; et al. (Frontiers in Neuroimaging)
IntroductionLow-intensity focused ultrasound (LIFU) is a form of neuromodulation that offers increased depth of penetrance and improved spatial resolution over other non-invasive techniques, allowing for modulation of otherwise inaccessible subcortical structures that are implicated in neuropsychiatric pathologies. The amygdala is a target of great interest due to its involvement in numerous psychiatric conditions. While prior works have found that LIFU sonication of the amygdala can alter resting-state neural activation, only a few studies have investigated whether LIFU can selectively modulate the amygdala during task-based fMRI.MethodsWe aimed to address these gaps in literature in a cohort of 10 healthy individuals. We utilized the well-validated Emotional Face Assessment Task (EFAT), which is designed to robustly engage the amygdala. We selected the fusiform gyrus and the thalamus as our non-target regional comparison measures due to their roles in facial and emotional processing. In succession, participants completed a pre-LIFU baseline fMRI, received 10-min of LIFU neuromodulation, and then repeated the baseline fMRI. To test our hypothesis, we conducted paired-samples t-tests assessing changes in amygdala, fusiform gyrus, and thalamic activation from pre to post scan.ResultsWe found that there was a significant decrease in left (t(9) = 2.286; p = 0.024) and right (t(9) = 2.240; p = 0.026) amygdala activation from pre-to-post sonication.DiscussionMeanwhile, there were no differences in activation of the left or right fusiform gyrus or thalamus. Our results indicate that LIFU of the amygdala acutely dampens amygdala reactivity during active socio-emotional processing.